Genetic and wind field analysis of wheat leaf rust (Puccinia triticina) dispersal: from winter sources in Gansu and Shaanxi to summer epidemics in China - Li, Hongfu; Zhao, Na; Zhang, Qinqin; Huang, Liang; Zhang, Hao; Gao, Li; Chen, Wanquan; Liu, Taiguo (Frontiers in Plant Science, 2025)
Wheat leaf rust caused by Puccinia triticina (Pt) is one of the most serious diseases affecting wheat worldwide. Given that China is the world’s largest wheat-producing country, there is a lack of comprehensive understanding regarding the temporal and spatial dynamics of wheat leaf rust epidemics. This study investigated the population structure of Pt across different wheat leaf rust epidemic seasons in Gansu and Shaanxi provinces. Samples were collected in the 2020 winter from Gansu and Shaanxi, and during the 2021 spring and summer from eight additional provinces: Shandong, Henan, Gansu, Shaanxi, Hubei, Yunnan, Guizhou, and Xinjiang. Population genetics analysis was conducted using 12 pairs of Simple sequence repeat (SSR) markers. The results indicated that the genetic diversity of the samples was highest in Shandong (SD) and Shaanxi in the 2020 winter (SN_20w), and Shaanxi in the 2021 summer (SN_21s), while Xinjiang (XJ) exhibited the lowest genetic diversity. Population structure analysis revealed six distinct genetic backgrounds across the 10 populations, with SN_20w and XJ showing greater genetic distances compared to other populations. There was less genetic differentiation and strong gene flow between pairwise populations of Henan (HA) and SN_21s, SD and Gansu in the winter of 2020 (GS_20w), Gansu in the summer of 2021 (GS_21s) and Hubei (HB), and GS_20w and HB, with six shared multi-locus genotypes detected among four pairwise populations. Integrating population genetic analysis, horizontal wind field analysis, topographic analysis, and the sampling timeline, this study concluded that the winter populations of Pt in the Guanzhong region experienced dominance shifts, with limited impact on the wheat leaf rust epidemic of 2021. In the 2021 epidemic season, two pathways of pathogen dispersal were proposed: (1) from the Guanzhong basin to Henan province; (2) through the Hanshui River Valley to Hubei province. These findings provide valuable insights into the spatial dynamics of wheat leaf rust and inform targeted prevention and control strategies.